Implementatif Konsep Amanah dalam Pengendalian Internal Keuangan Masjid (Studi Kasus Masjid Baiturrahman Padang Panjang) - Abdul Rahim A; Ismi Hamdani; Awaluddini Marifatullah; Syamsurizal Syamsurizal (Journal on Education, 2023)
A mosque is a non-profit organization that is more likely to be established for the purpose of the public interest, of course it is demanded that it must be able to produce financial information that has power and transparency that accurate Of course, in producing power of transparency strong, internal control over financial management of mosques is very necessary The purpose of this research is to know and study the implementation of the concept of trust in internal control, financial reports mosques The research method used is qualitative and descriptive The results of the research explain that the financial administration of the mosque, al Baiturrahman, is carried out with an attitude of transparency to the congregation, so that the administrators of the mosque are able to regulate and manage finances mosque and get full trust from people Money that goes out and comes in is always recorded regularly and neatly and reported periodically The process of internal control at the mosque, al Baiturrahman, is still being used, the process is simple hat every activities process receiving and spending routine as well as not outine always carried out by way holding meeting previously before processing disbursement funds mosque